Comparative study of immediate post placental vaginal versus intra caesarean insertion of copper T380A - Dhaduti, Rashmi; Deshpande, Sonali; Gadappa, Shrinivas; Wanjare, Nutan; Pund, Sandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The study was carried out to compare modes of PPIUCD that is safety, removal and expulsion rates of immediate post placental vaginal versus intracaesarean insertion of copper T380A. Methods: This was an interventional study conducted from January 2015 to December 2016 in Department of Obstetrics and Gynaecology, Government Medical College and Hospital, Aurangabad. This study involved participants who accepted PPIUCD in antenatal period and delivered in Government Medical College and Hospital, Aurangabad. Copper T380A was inserted vaginally after taking consent in 50 postpartum mothers within 10 minutes of normal vaginal delivery and 50 women who were undergoing caesarean section for obstetric indications who accepted copper T380A from contraceptive basket. Chorioamnionitis, prolonged premature rupture of membranes, unresolved postpartum hemorrhage, major medical disorder and participants who were lost to follow up were excluded. Antibiotic cover was given for 5 days. Participants were followed up either personally or telephonically at 6 weeks, 6 months or earlier if they had any complaints. Results: Among 50 post placental vaginally copper T380A inserted participants, 6(12%) had menstrual disturbance and pain abdomen each. One participant (2%) had infection vaginitis. Among 50 intracaesarean copper T380A inserted participants, 3 (6%) had menstrual disturbance and pain abdomen each. 6 (12%) had missing strings. Missing strings which was seen only in intracaesarean group was statistically significant when compared to post placental vaginal group. Expulsion was seen only in post placental vaginally copper T380A inserted participants (4 out of 50). There was no statistically significant difference in expulsion & removal rates of both the groups. Conclusions: Both modes of PPIUCD insertion were equally safe for participants except for missing strings which was seen more in intracaesarean group and was statistically significant.